The Magisterium of the Church and the Digital World: Antiqua et Nova - Domaszk, Arkadiusz (Prawo Kanoniczne, 2026)
Artificial intelligence is typically associated with the domain of emerging technologies. Yet these developments profoundly influence the functioning of the human world as a whole. The Catholic Church, for its part, is actively engaged in the contemporary debate on these issues. It is within this context that the Note Antiqua et Nova, published on 28 January 2025, was prepared. This study offers a concise overview of the Magisterium’s teaching on the Internet and its use. It then sketches the key statements on artificial intelligence issued by the Magisterium prior to Antiqua et Nova. Next, it presents the content of the 2025 Note, with particular attention to the section devoted to education. The final part of the study attempts to relate these new technological challenges to the sphere of canon law, examining whether—and to what extent—the emerging technologies of artificial intelligence ought to be regulated by ecclesiastical norms. Artificial intelligence and its tools first require thorough understanding and careful study. Only then can one consider their practical application within the digital realm, including for evangelization, while taking into account both their advantages and their risks. At the same time, the Magisterium reiterates fundamental principles to ensure that the foundations of Christian anthropology and the moral dimension of using digital tools are not overlooked—so that such technologies truly serve the good of the human person and of society. There is also a need to develop appropriate canonical regulations, particularly in the field of education, in light of the Church’s responsibility for Catholic schools, Catholic universities, and ecclesiastical institutions.